Behavioral Theory: The Missing Ingredient for Digital Health Tools to Change Behavior and Increase Adherence - Klonoff, David C. (J Diabetes Sci Technol, 2019)
Behavioral theory is an important factor for designing digital health tools for diabetes to increase adherence to treatment. Many digital health products have not incorporated this method for achieving behavior change. This oversight might explain the disappointing outcomes of many products in this class. Four theories reported to be capable of enhancing the performance of digital health tools for diabetes include (1) Integrate, Design, Assess, and Share (IDEAS); (2) the Behaviour Change Wheel; (3) the Information-Motivation-Behavioral skills (IMB) model; and (4) gamification. Well-designed digital health tools are most likely to be effective if they are deployed in a patient-centered care setting established upon principles of sound behavioral theory. Behavioral theory can increase the effectiveness of digital tools and promote a receptive environment for their use.